Transmembrane domain of the envelope gene of a polycythemia-inducing retrovirus determines erythropoietin-independent growth. - Chung, S W (1989)
Both the polycythemia-inducing and the anemia-inducing strains of Friend spleen focus-forming virus can induce acute erythroleukemia in susceptible adult mice. However, only cells infected with the polycythemia-inducing strain become erythropoietin-independent for proliferation and differentiation. The sequences responsible for the altered erythropoietin responsiveness have previously been localized to a 678-base-pair EcoRI-Cla I fragment at the 3' end of the envelope gene. This region is now further analyzed by dividing it into two fragments by using the Fok I restriction site. Two recombinants were made by replacing either the 558-base-pair EcoRI-Fok I or the 113-base-pair Fok I-Cla I env gene fragments from the anemia-inducing strain of spleen focus-forming virus with sequences derived from the polycythemia-inducing strain. Our results indicate that the 113-base-pair Fok I-Cla I fragment, which encodes primarily the transmembrane domain of the envelope protein, determines erythropoietin-independent growth.